A COMPARISON OF DISCRETE AND CONTINUOUS INTRUSION MODELS FOR THE THERMAL STRUCTURE OF THE PLATES - Royden, L; Parsons, B (1982)
We have obtained the temperature solution for a thermal model of the plates in which material is emplaced at discrete intervals rather than spreading continuously. The time-averaged heat flux and integrated heat flux for this discrete instrusion model are finite everywhere, differing from that given by a one-dimensional cooling model within a few intrusion widths of the ridge axis. In the limit as the intrusion width and period of emplacement tend to zero the temperature solution away from the ridge axis becomes that given by a modified plate model where a thermal balance boundary condition instead of a constant temperature condition is applied at the ridge axis. The integrated heat loss from a limited age interval about the ridge differs negligibly from that given by the one-dimensional cooling model or the modified plate model provided the interval extends more than two intrusion widths from the ridge axis.-Authors